Treatment of glioblastoma patients with personalized vaccines outside clinical trials: Lessons ignored? - Tabatabai, Ghazaleh; Platten, Michael; Preusser, Matthias; Weller, Michael; Wick, Wolfgang; van den Bent, Martin (Neuro-Oncology, 2025)
The treatment of patients with glioblastoma remains a challenge. Several large clinical trials of the last decades have failed and had—in retrospect—been built on over interpreted uncontrolled or inadequately controlled phase II trials or retrospective case series. Despite this disappointing experience and critical reviews, the temptation to demonstrate the value of novel experimental treatments without randomized trials using external control data and then to report a positive outcome compared to those “historical” or “external” controls remains. Recently reported “real-world observation” of glioblastoma patients treated with a personalized peptide vaccine led by a German for-profit center1 is yet another example of such an attempt. As we anticipate misunderstandings and erroneous conclusions from this publication, we reviewed the data and the conclusions presented from a clinical and translational science perspective.
Online veröffentlicht: 19. November 2024
Gesehen am 14.04.2025